Exploring policy coherence to understand limited progress of gender and social inclusion in the energy sector: the case of Nepal - Buchy, Marlene; Shakya, Shristi (Elsevier, 2024)
Goal 7 of the Sustainable Development Goals (SDGs) aims to ensure access to affordable, reliable, sustainable, and modern energy for all by 2030 but securing universal access to energy supplies remains a challenge worldwide. There is increased recognition that gender and social inclusion (GESI) is critical for the transition towards low-carbon energy.